Adiposity and the risk of thyroid nodules with a high-suspicion sonographic pattern: a large cross-sectional epidemiological study - Lai, Xingjian (J Thorac Dis, 2019)
BACKGROUND: To our knowledge, no previous studies have evaluated the association between obesity and the risk of thyroid nodules with a high-suspicion sonographic pattern defined by the 2015 American Thyroid Association management guidelines for adult patients with thyroid nodules and differentiated thyroid cancers. In this large cross-sectional epidemiological study, we investigated whether a positive association existed between anthropometric measurements and the risk of thyroid nodules. METHODS: In total, 10,504 individuals from two towns in northern China were enrolled between May to September 2016. The height and weight were measured and the body mass index (BMI), body fat percentage (BFP), and body surface area (BSA) were calculated. A logistic regression model was used to estimate age-, sex-, and study site-adjusted odds ratios (ORs) and confidence intervals (CIs) for each of the anthropometric measurements with respect to the risk of thyroid nodules. RESULTS: The final analyses included 9,096 participants, among whom 3,614 (39.7%) had thyroid nodules and 365 (4.0%) had thyroid nodules with a high-suspicion sonographic pattern. An increased risk of any thyroid nodules was associated with greater height, weight, BFP, and BSA in both men and women. Compared with the lowest quartile of BFP, the ORs for the highest quartile were 1.33 (95% CI: 1.09–1.62) in women and 1.89 (95% CI: 1.35–2.65) in men. An increased risk of thyroid nodules with a high-suspicion sonographic pattern was associated with greater weight, BMI, BFP, and BSA in both men and women. Compared with the lowest quartile of BFP, the ORs for the highest quartile were 2.19 (95% CI: 1.32–3.64) in women and 3.10 (95% CI: 1.31–7.36) in men. CONCLUSIONS: Our results demonstrated that BFP was the most pronounced anthropometric factor associated with an increased risk of any thyroid nodules and thyroid nodules with a high-suspicion sonographic pattern.